2023
DOI: 10.3390/ijerph20043746
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ventilation Measures on the Airborne Risk of Infection in Schools: A Scoping Review

Abstract: Objectives: To review the risk of airborne infections in schools and evaluate the effect of intervention measures reported in field studies. Background: Schools are part of a country’s critical infrastructure. Good infection prevention measures are essential for reducing the risk of infection in schools as much as possible, since these are places where many individuals spend a great deal of time together every weekday in a small area where airborne pathogens can spread quickly. Appropriate ventilation can redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Peer-reviewed studies conducted in the past 2 years have evaluated the contribution of ventilation in schools to reducing COVID-19 transmission as a component of multilayered strategies. 18,[38][39][40][41] Buonanno et al 38 showed that mechanical ventilation installed in 56 Italian schools reduced infection risk by at least 74% compared to over 10,000 classrooms with only natural ventilation. A recent literature review reinforced this finding, defining a maximum acceptable average value for CO 2 of 1,000 ppm, which should be lowered to 800 ppm during a pandemic, using carbon dioxide as a surrogate for infection risk.…”
Section: School Buildingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Peer-reviewed studies conducted in the past 2 years have evaluated the contribution of ventilation in schools to reducing COVID-19 transmission as a component of multilayered strategies. 18,[38][39][40][41] Buonanno et al 38 showed that mechanical ventilation installed in 56 Italian schools reduced infection risk by at least 74% compared to over 10,000 classrooms with only natural ventilation. A recent literature review reinforced this finding, defining a maximum acceptable average value for CO 2 of 1,000 ppm, which should be lowered to 800 ppm during a pandemic, using carbon dioxide as a surrogate for infection risk.…”
Section: School Buildingsmentioning
confidence: 99%
“…A recent literature review reinforced this finding, defining a maximum acceptable average value for CO 2 of 1,000 ppm, which should be lowered to 800 ppm during a pandemic, using carbon dioxide as a surrogate for infection risk. 41 The authors concluded that every classroom should have mechanical ventilation, which also prevents temperature extremes and improves students' abilities to concentrate. 41 A literature review by McLeod et al 40 suggested 1,000 ppm of CO 2 should never be exceeded over a teaching hour.…”
Section: School Buildingsmentioning
confidence: 99%
See 3 more Smart Citations